2021
DOI: 10.3390/cancers13143554
|View full text |Cite
|
Sign up to set email alerts
|

Risk Classification for Overall Survival by the Neutrophil–Lymphocyte Ratio and the Number of Metastatic Sites in Patients Treated with Pembrolizumab—A Multicenter Collaborative Study in Japan

Abstract: Pembrolizumab has emerged as the new standard of care in patients with platinum-refractory metastatic urothelial carcinoma (mUC), whereas the optimal risk stratification to predict survival outcomes is still controversial. We examined a risk model for overall survival (OS) in mUC treated with pembrolizumab using our multi-institutional dataset (212 patients). The median age was 72 years old. Median OS from the initiation of pembrolizumab treatment was 11.7 months. The objective response rate (ORR) was 26.4%. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Some efficacy of bone-modifying agents, such as zoledronic acid or denosumab, has been reported for SREs, but it is not sufficient [ 14 ]. Although the research direction of ICIs for ur/mUC is scattered, there are few reports focusing on bone metastasis, and it may be difficult to evaluate because other therapeutic modalities, such as radiation therapy, may be added [ 13 , 15 , 16 ]. The advent of pembrolizumab has not led to significant progress in the treatment of bone metastasis ( Figure 2 ), and treatment and maintenance of the QOL of patients with UC-related bone metastases should be investigated further in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Some efficacy of bone-modifying agents, such as zoledronic acid or denosumab, has been reported for SREs, but it is not sufficient [ 14 ]. Although the research direction of ICIs for ur/mUC is scattered, there are few reports focusing on bone metastasis, and it may be difficult to evaluate because other therapeutic modalities, such as radiation therapy, may be added [ 13 , 15 , 16 ]. The advent of pembrolizumab has not led to significant progress in the treatment of bone metastasis ( Figure 2 ), and treatment and maintenance of the QOL of patients with UC-related bone metastases should be investigated further in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of these therapies is not uniform across all patients, necessitating the identification of reliable predictive biomarkers to guide treatment decisions and optimize clinical outcomes. 17 NLR in peripheral blood is a cost-effective and widely accessible biomarker significantly associated with survival outcomes and response rates following CPIs treatment across multiple cancer types. 9 Interestingly, a previous study showed that the prognostic value of NLR appears to be enhanced when combined with TMB, another established biomarker of response to CPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up protocol was described in the previous report. 8 Briefly, follow-up CT for detecting any findings suspected of disease progression was scheduled every 6 weeks during the follow-up, and treatment response of pembrolizumab was assessed by the Response Evaluation Criteria in Solid Tumors (RECIST) V.1.1. 15 Re-evaluation using MRI, bone scintigraphy, and positron emission tomography/CT (PET/CT) were further performed when necessary for the definitive diagnosis of immune-confirmed disease progression.…”
Section: Methodsmentioning
confidence: 99%
“… 7 Since then, pembrolizumab has been widely used in large numbers of patients worldwide as well as in Japan. 8 9 …”
Section: Introductionmentioning
confidence: 99%